2012
DOI: 10.1523/jneurosci.5319-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase Inhibition Abolishes LTP Generation in Female But Not in Male Mice

Abstract: Inhibitors of aromatase, the final enzyme of estradiol synthesis, are suspected of inducing memory deficits in women. In previous experiments, we found hippocampal spine synapse loss in female mice that had been treated with letrozole, a potent aromatase inhibitor. In this study, we therefore focused on the effects of letrozole on long-term potentiation (LTP), which is an electrophysiological parameter of memory and is known to induce spines, and on phosphorylation of cofilin, which stabilizes the spine cytosk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
139
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(157 citation statements)
references
References 61 publications
14
139
2
2
Order By: Relevance
“…In line with this idea, the effect of LTZ timescale detected on VOR adaptation could indicate a rapid E2 impact on the molecular pathways leading to synaptic plasticity underling motor memory. This is supported by data demonstrating an effect of LTZ on LTP induction preceding structural remodeling at the synaptic level (Vierk et al 2012(Vierk et al , 2014.…”
Section: Neurosteroid E2 Is Necessary For Vor Adaptationsupporting
confidence: 55%
See 1 more Smart Citation
“…In line with this idea, the effect of LTZ timescale detected on VOR adaptation could indicate a rapid E2 impact on the molecular pathways leading to synaptic plasticity underling motor memory. This is supported by data demonstrating an effect of LTZ on LTP induction preceding structural remodeling at the synaptic level (Vierk et al 2012(Vierk et al , 2014.…”
Section: Neurosteroid E2 Is Necessary For Vor Adaptationsupporting
confidence: 55%
“…The modulatory role of neurosteroid E2 on synaptic plasticity has been demonstrated in vestibular nuclei, basal ganglia and hippocampus by acute as well as long-lasting inhibition of the E2 pathway, which impairs LTP induction (Grassi et al 2009a(Grassi et al , b, 2010(Grassi et al , 2012Pettorossi et al 2013;Scarduzio et al 2013;Vierk et al 2012Vierk et al , 2014. Consistent with these findings, it has been shown that acute inhibition of E2 synthesis also exerts rapid effects on spatial learning, working memory and fear extinction (Alejandre-Gomez et al 2007;Graham and Milad 2014;Moradpour et al 2006).…”
Section: Introductionmentioning
confidence: 81%
“…In neonatal hippocampal slice cultures, aromatase inhibition decreased expression of synaptic proteins, dendritic spine density, and presynaptic boutons (Kretz et al 2004;Prange-Kiel et al 2006). A recent in vivo study found that systemic injections of the aromatase inhibitor letrozole were associated with impaired LTP and transient dephosphorylation of cofilin in gonadally intact male and female rats, as well as in ovariectomized rats (Vierk et al 2012). However, the deficits were considerably more striking for females than for males (Vierk et al 2012), perhaps indicating a greater reliance on hippocampally synthesized E 2 for LTP and spine alterations in females.…”
Section: Hippocampally Synthesized E 2 and Memorymentioning
confidence: 99%
“…A recent in vivo study found that systemic injections of the aromatase inhibitor letrozole were associated with impaired LTP and transient dephosphorylation of cofilin in gonadally intact male and female rats, as well as in ovariectomized rats (Vierk et al 2012). However, the deficits were considerably more striking for females than for males (Vierk et al 2012), perhaps indicating a greater reliance on hippocampally synthesized E 2 for LTP and spine alterations in females. The finding that mature spines, thin spines, and spine synapses were reduced by letrozole in females, whereas only thin spines were reduced by letrozole in males may support this conclusion (Vierk et al 2012).…”
Section: Hippocampally Synthesized E 2 and Memorymentioning
confidence: 99%
“…These results suggest that estradiol rapidly enhances synaptic transmission and plasticity in the hippocampus, possibly through local synthesis of 17b-estradiol (Smejkalova and Woolley 2010). In fact, inhibition of aromatase, the final enzyme of local estradiol synthesis, with letrozole, significantly disrupted LTP in slices from female, but not from male rats (Vierk et al 2012). The lack of effect of DR/C/K3 or interaction of DR/C/K3 expression and ovarian hormones on LTP, however, argues against a role for DR/C/K3 in local synthesis of estradiol or rapid effects of estradiol.…”
Section: Synaptic Plasticity and Physiologymentioning
confidence: 82%